2017
DOI: 10.1084/jem.20161190
|View full text |Cite
|
Sign up to set email alerts
|

Breaching peripheral tolerance promotes the production of HIV-1–neutralizing antibodies

Abstract: Schroeder et al. demonstrate that when peripheral tolerance is relaxed, tier 2 HIV-1–neutralizing antibodies can be elicited and identify new autoreactive antibody specificities against histone H2A capable of neutralizing tier 2 HIV-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 93 publications
3
49
1
Order By: Relevance
“…The self antigens recognized by these HIV-1 bnAbs include the enzymes kynureninase and ubiquitin ligase E3A, SF3B3 splicing factor [19, 20], phospholipids (e.g. cardiolipin) [21], dsDNA [17] and, recently, histone H2A [22]. Why some bnAbs display autoreactivity remains speculative, although evidence exists for host mimicry by HIV-1 and as a possible mechanism used by the virus to avoid adaptive immunity [20].…”
Section: Hiv-1 Broadly Neutralizing Antibodies (Bnabs) Display Unusuamentioning
confidence: 99%
See 3 more Smart Citations
“…The self antigens recognized by these HIV-1 bnAbs include the enzymes kynureninase and ubiquitin ligase E3A, SF3B3 splicing factor [19, 20], phospholipids (e.g. cardiolipin) [21], dsDNA [17] and, recently, histone H2A [22]. Why some bnAbs display autoreactivity remains speculative, although evidence exists for host mimicry by HIV-1 and as a possible mechanism used by the virus to avoid adaptive immunity [20].…”
Section: Hiv-1 Broadly Neutralizing Antibodies (Bnabs) Display Unusuamentioning
confidence: 99%
“…As an extension of these observations, a recent study in our lab has demonstrated that autoimmune prone mice, with known defects in both central and peripheral tolerance, are able to produce neutralizing antibodies against tier 2 HIV-1 subtypes [22]. Interestingly, the lupus prone B6.Sle123 mouse strain, which harbors 3 chromosomal regions from the autoimmune NZM2410 strain on the C57BL/6 genetic background [59], produced tier 2 HIV-1 neutralizing antibodies following alum and TLR immunization alone, in the absence of Env ([22] and unpublished data).…”
Section: Immunological Tolerance As a Barrier To Protective Hiv-1 Hummentioning
confidence: 99%
See 2 more Smart Citations
“…It has been speculated that some pathogens, including HIV, evade immune detection by exploiting “holes” in the B cell repertoire that are created by B cell tolerance mechanisms. Indeed, breaching peripheral B cell tolerance may actually facilitate generation of bNAbs [60]. The autoreactive VH4–34 BCR is expanded in the memory B cell compartment of malaria patients, and VH4–34-derived antibodies rise during acute malarial infection (though the extent of their protective capacity is unclear) [61].…”
Section: Introductionmentioning
confidence: 99%